Meta-analysis of gene expression for development and validation of a diagnostic biomarker panel for Oral Squamous Cell Carcinoma. (October 2019) - Makarov, Vladimir; Gorlin, Alex
Graphical abstract: Highlights Present a diagnostic biomarker panel for Oral Squamous Cell Carcinoma. Use meta-analysis of gene expression data and sort features with a dichotomy power metric. Results are reproducible - concordant with earlier studies. Explain irreproducibility of molecular biomarkers for this cancer seen in earlier studies. Abstract: We use a newly developed feature extraction and classification method to analyze previously published gene expression data sets in Oral Squamous Cell Carcinoma and in healthy oral mucosa in order to find a gene set sufficient for diagnoses. The feature selection technology is based on the relative dichotomy power concept published by us earlier. The resulting biomarker panel has 100% sensitivity and 95% specificity, is enriched in genes associated with oncogenesis and invasive tumor growth, and, unlike marker panels devised in earlier studies, shows concordance with previously published marker genes.